PRODUCTION OF ‘NIAGARA BRANCA’ AND ‘CONCORD’ VARIETIES SUBMITTED TO TWO HARVESTS BY SEASON AT DEPRESSÃO CENTRAL OF RIO GRANDE DO SUL - ANZANELLO, Rafael; SOUZA, Paulo Vitor Dutra de; GONZATTO, Mateus Pereira (Scientia Agraria, 2008)
The adequate pruning management of grapevine permits to change its fenology, modifying the crop periods and creating conditions for two annual harvests. A winter pruning period (08/08/05) and two periods of summer pruning (04/11/05 and 02/12/05) were evaluated in order to obtain two annual harvests, using Niagara Branca and Concord grape varieties (both Vitis labrusca). This experiment was performed during the 2005/2006 season in grapevines conducted by cordon training in Eldorado do Sul county, Rio Grande do Sul, Brazil. Variables associated to fenology, plant production, weight of grapes, total soluble solids, total titratable acidity and ratio total soluble solids by total titratable acidity related to harvests were analyzed. The fenology of plants pruned in winter was 156 days for ‘Niagara Branca’ and 161 days for ‘Concord’, and the harvest was performed around January, 15th. Regarding the summer pruning performed on 04/11/05 and 02/12/05, fenology cycle of shoots was 127 and 113 days for the ‘Niagara Branca’ and 134 and 120 days for the ‘Concord’, respectively. Harvest was realized in middle April, 15th. The summer pruning realized in 04/11/05 provided higher production per plant and grapes of higher weight, independent of cultivar, when compared to the 02/12/05 pruning. Fruit quality was similar among the harvests, with significant differences between cultivars expressed by smaller total titratable acidity and higher ratio of total soluble solids by total titratable acidity for the ‘Niagara Branca’.